Testing non-linear effect of urbanization on environmental degradation: Cross-country evidence - Talib, Mirza Nouman Ali; Hashmi, Shujahat Haider; Aamir, Muhammad; Khan, Muhammad Asif (Frontiers in Environmental Science, 2022)
The contribution of structural transformation and urban development is considered crucial for the long run socio-economic growth but has adversely affected environmental sustainability over last few decades. This empirical research makes an innovative and holistic addition to the prior literature by examining the non-linear effect of economic growth and urban dynamics on environmental degradation in a comprehensive panel data of 66 countries and across respective income groups for the period 1990–2016. For empirical analysis, the robust econometric methods of two-way fixed effects (2W-FE), panel fully modified ordinary least squares (PFMOLS), and Driscoll-Kraay regressions have been applied to account for all econometric issues. The study unveils the bell-shaped effect of economic growth on environmental degradation which confirms the Environmental Kuznets Curve (EKC) and structural change hypotheses. The results of this study signifies the inverted U influence of urbanization and urban agglomerations on CO2 emissions and hence supports Ecological Modernization Theory (EMT). Our empirical findings also unfold the heterogeneous non-linear effects of urban dynamics across various income categories of selected economies. By employing the heterogeneous Dumitrescu and Hurlin (D-H) (Granger non-causality tests), the findings of this study confirm the prior estimations and establish significant unilateral and bilateral causal nexus of structural change and urban dynamics with environmental degradation. By verifying the existence of Environmental Kuznets Curve phenomenon in Low and Lower Middle Income (LLMI) and Upper Middle Income (UMI) group countries, this study necessitates for the policy makers to adopt the eco-friendly industrial and energy policies for the long run social, economic and environmental sustainability.